2017
DOI: 10.1017/s1041610217002393
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Glutamyltransferase (GGT) as a biomarker of cognitive decline at the end of life: contrasting age and time to death trajectories

Abstract: This is the first longitudinal study to report on significant associations in late life between GGT, cognitive performance and dementia. Further research is needed to examine the underlying mechanisms of GGT as a marker of age-related cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Kunutsor and Laukkanen 16 demonstrated for the first time that elevated GGT level in midlife is associated with risk of dementia in the male population aged 42 to 61 years in Finland. Praetorius Bjork and Johansson 17 also reported the association among GGT, cognitive performance, and dementia in late life. Nevertheless, these studies included limited populations, such as male or elderly only cohorts, with relatively small sizes, and did not account for variability in GGT.…”
Section: Introductionmentioning
confidence: 95%
“…Kunutsor and Laukkanen 16 demonstrated for the first time that elevated GGT level in midlife is associated with risk of dementia in the male population aged 42 to 61 years in Finland. Praetorius Bjork and Johansson 17 also reported the association among GGT, cognitive performance, and dementia in late life. Nevertheless, these studies included limited populations, such as male or elderly only cohorts, with relatively small sizes, and did not account for variability in GGT.…”
Section: Introductionmentioning
confidence: 95%
“…On correction for regression dilution, the corresponding estimates were respectively 1.51 and 1.37 per 1 SD increase in long-term serum GGT. In another recent longitudinal study conducted in older individuals, Praetorius Björk and Johansson demonstrated higher GGT concentrations to be associated with cognitive decline prior to death and vascular dementia in late life ( Praetorius Bjork and Johansson, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that serum GGT within the normal range is an early marker for oxidative stress (34). Oxidative stress has been suggested to be associated with frailty (35) and increased GGT levels in later life (80 years and older) were associated with cognitive decline (36). However, we unexpectedly observed lower instead of higher GGT levels in cognitively frail women compared to controls, indicating that cognitive frail women might have less oxidative stress.…”
Section: Discussionmentioning
confidence: 99%